Contribution to a South Indian marine algal flora - II - Boergesen, F. (New York, NY Wiley-LIss Inc., 1991)
Contents: Contributions to a South Indian Marine Algal Flora III. Some Indian Rhodophyceae, especially from the shores of the Presidency of Bombay. Some Indian green and brown algae especially from the shores of the Presidency of Bombay III. Some marine algae from Ceylon
Keywords: Marine algae